Single-Input Fuzzy-Sliding Mode Control for an Underactuated Quadrotor Craft - Abro, G.E.M. (Institute of Electrical and Electronics Engineers Inc., 2020)
This work presents performance analysis between conventional fuzzy-based sliding mode control (F-SMC) and single-dimension fuzzy-sliding mode control (SDF-SMC) for an underactuated quadrotor craft. It has been observed that fuzzy logic control (FLC) can resolve various issues of sliding mode controller (SMC) for the quadrotor, such as reduction in chattering noise or Zeno phenomenon. However, FLC increases required computational power and processing time, which directly rely on the list of rules defined for the FLC. These rules trigger the gains of the SMC. This paper presents an approach to convert the conventional FLC two-dimensional rule-based table into a single-dimension table, leading to a control algorithm referred to as single-input fuzzy-sliding mode control. Numerical simulation work has been implemented on MATLAB-Simulink software, which demonstrates the same control performance of the SDF-SMC as the conventional F-SMC, but with the improvement of reduced computational power and processing time. Â© 2020 IEEE.